STUDI PENGARUH KEDALAMAN LUBANG TEMBAK TERHADAP FRAGMENTASI HASIL PELEDAKAN PADA PT. PAMAPERSADANUSANTARA SITE PT. KIDECO KALIMANTAN TIMUR (Jurnal Geomine, 2015)
Hole depth blows up really ascendant on fragmentasi usufructs detonation, where gets hole depth shallow blow up therefore boulder which is resulted the greaterThis type of data consists of primary data and secondary data. Primary data consists of geometric data of drilling, the data fragmentation, while the secondary data comprises geological of data research area, topographic maps and geological map of the study area, company profiles required in a research report.For data collection was done by direct measurement of the depth of the hole will be filled explosive and interviews with the crew and supervisor during the activity blasting and obtained an average depth of any location in South Roto PIT is: 7F IB 4/6 (7.7 m), 7A IB 4/5 (7.6 m), 8D2 18 WALL (7.7 m), 8C2 CB (7.8 M), 2C3 PILLAR 18 (7.7 m), 3F IB 13 (7.3 m), 7B2 CB (7.8 m).From the fragmentation and different rock factor average: 7F IB 4/6 (7.39%), (5.21), 7A IB 4/5 (24.08%), (6.45), 8D2 18 WALL (8.38%), (5.21), 8C2 CB (5.68%), (5.04), 2C3 PILAR 18 (9.23%), (5.06), 3F IB 13 (3.13%), (4.46), 7B2 CB (14.28%), (5.86). From the above results that the depth and different rock factor will result in different fragmentation and blast hole that produced will be better.